Implementation suggestions for shared decision-making: results from a comparative study of inpatients and outpatients experience surveys - Cindy Yue Tian; Eliza Lai-Yi Wong; Hong Qiu; Shimeng Liu; Kailu Wang; Yan Wei; Annie Wai-Ling Cheung; Yingyao Chen; Eng-Kiong Yeoh (BMC Health Services Research)
Abstract Background Shared decision-making (SDM) is crucial in patient-centered healthcare services, but its integration into routine medical care remains limited. This study aimed to investigate patients’ experience with SDM in both outpatient and inpatient settings, exploring how the quality of care provided by doctors and patient’s trust in doctors influence SDM across different contexts. Methods This study utilized data from the regional cross-sectional surveys, including the 2019 Inpatient Experience and the 2021 Specialist Outpatient Experience survey in Hong Kong. Multivariable logistic regression and path analysis were conducted. Results A total of 20,675 participants were included (inpatients: n = 8,275; outpatients: n = 12, 400) in this study. The results indicated that inpatients perceiving better quality of doctor’s care were significantly more likely to participate in SDM (OR = 1.29, 95%CI = 1.26–1.47, p < 0.001), with trust in doctors significantly moderating this association. Conversely, among outpatients, a higher quality of doctor’s care was significantly associated with decreased SDM involvement (OR = 0.91, 95% CI = 0.88-1.00, p = 0.04), with trust in doctors serving as a mediator in suppressing this association. Additionally, both subsets indicated that females, the elderly, individuals with good health status, less-educated people, and those living alone were less likely to engage in SDM. Conclusion These findings underscore the importance of tailoring SDM implementation to specific contexts, acknowledging the different challenges within outpatient and inpatient settings. Building trust is key to promoting SDM, with added support for vulnerable groups to ensure their involvement in decision-making.